(untitled) (Ustozlar uchun, 2025)
This research examines how globalization has influenced contemporary English literature. Global cultural exchange, migration, technological advancement, and the dominance of English as a global lingua franca have reshaped literary themes, styles, and identities. Modern writers incorporate multicultural perspectives, hybrid identities, and transnational experiences into their works. The study highlights how globalization broadens literary boundaries while also raising concerns about cultural homogenization.